No evidence that within-group male relatedness reduces harm to females in Drosophila - Hollis, Brian (Ecol Evol, 2015)
Conflict between males and females over whether, when, and how often to mate often leads to the evolution of sexually antagonistic interactions that reduce female reproductive success. Because the offspring of relatives contribute to inclusive fitness, high relatedness between rival males might be expected to reduce competition and result in the evolution of reduced harm to females. A recent study investigated this possibility in Drosophila melanogaster and concluded that groups of brothers cause less harm to females than groups of unrelated males, attributing the effect to kin selection. That study did not control for the rearing environment of males, rendering the results impossible to interpret in the context of kin selection. Here, we conducted a similar experiment while manipulating whether males developed with kin prior to being placed with females. We found no difference between related and unrelated males in the harm caused to females when males were reared separately. In contrast, when related males developed and emerged together before the experiment, female reproductive output was higher. Our results show that relatedness among males is insufficient to reduce harm to females, while a shared rearing environment – resulting in males similar to or familiar with one another – is necessary to generate this pattern.